Retrofit through Add-ons: the ABRACADABRA strategy as an opportunity for the energy renovation of private-owned and public buildings - Emmanuelle Causse; Annarita Ferrante; Lorna Dragonetti; Giovanni Semprini; Spyridon Pantelis; Sorcha Edwards; Julien Dijiol (Tema, 2018)
The EU environmental and energy policies are promoting energy efficiency retrofit actions, in spite of the fact that the renovation rate in the construction sector is very low. The ABRACADABRA project aims to activate a deep renovation market through volumetric additions (add-ons), including one of the most challenging sectors, the social housing. In order to demonstrate how the densification action could be an effective solution to promote energy efficiency interventions and new business models with the scope to shorten the payback time of renovation investments (both at building and urban scale), four different buildings in different urban contexts have been analysed. The simulation made on these case studies is divided in three steps: an architectural feasibility study, an energy saving analysis and a payback time calculation; in this last phase of the study the financial assumptions are fundamental. The real estate values like the sale and the rental rate, as well as the social values were well-thought-out and combined in order to find the best opportunity for profits and the shortest payback time. Moreover, additional issues were taken into account regarding the regulatory aspects and the technical feasibility barriers for this type of approach. Implementing this strategy means to add new units on the rooftop or on the side of an existing building, and this might face obstacles, such as urban regulation restrictions and the consensus among tenants or owners. To overcome these mainly social obstacles, the project promotes new policy recommendations that public authorities could adopt and approve and also counterbalanced measures to help tenants/owners accept and embrace the ABRA strategy.